Study on bonding and chemical properties of coastal plastics waste - Helmy Muhamad, Khairi (2012)
The study was conducted to characterize the chemical and bonding properties of coastal plastics waste. Growing of economic, human activity and industrial procedure are resulting in the increased of the plastics wastes. Plastics waste generates cause major challenge in waste handling because of the varying properties due to degradation. Furthermore, the harmful effect and toxical hazard of plastics is a real threat to the health and environment. In order to study the properties, two method of testing are used. The samples are sorted base on their four types of plastics. The type of plastics that were used in this study was PVC (Polyvinyl Chloride), PS (Polystyrene), PET (Polyethylene Terephthalate) and PP (Polypropylene). The samples of plastics that have been sorted then were shred using shredding machine. All the shredded samples were fed into the extrusion machine to get the long-shape of plastics which later pelletized using pelletizing machine. The testing methods involve in this study were TGA (Thermogravimetric) and FTIR (Fourier Transform Infrared Spectroscopy). The result obtained for FTIR analysis shows the different of bonding between coastal and virgin plastics. Other group of homologous series was found in the bonding of coastal plastics waste. The resulted data for TGA analysis show the higher value of thermal degradation for coastal plastics waste compared to virgin plastics. Sample of PVC, PS PET and PP was degrading at temperature of 357.77oC, 384.25oC, 397.97o C and 362.61oC which is much higher than the virgin plastics that degrade at temperature of 333oC, 330oC, 265oC and 315oC. It can be concluded that the coastal plastics waste differ from the virgin plastics in term of bonding and temperature resistant. It is due to the long exposure to the sun and presence of other minerals on coastal plastics waste. This study shows that the coastal plastics waste have an advantages and unique properties compared to the virgin plastics. This study will provide foundation for future research on desirable method to handle the coastal plastics waste. It will enable for greater research and their potential to be used in technologies of plastics recycling.